Effects and Molecular Mechanism of Single-Nucleotide Polymorphisms of MEG3 on Porcine Skeletal Muscle Development - Yang, Rui; Liu, Yinuo; Cheng, Yunyun; Wang, Chunli; Song, Jie; Lu, Guanhong; Feng, Tianqi; Wang, Siyao; Sun, Xiaotong; Meng, Jilun; Hao, Linlin (Frontiers in Genetics, 2021)
Long noncoding RNA Maternally Expressed Gene 3 (MEG3) was reported to be a crucial regulator in skeletal muscle development. Some single-nucleotide polymorphisms (SNPs) mutants in MEG3 had strong associations with meat quality traits. Nevertheless, the function and mechanism of MEG3 mutants on porcine skeletal muscle development has not yet been well demonstrated. In this study, eight SNPs were identified in MEG3 of the fat-type pig breeds and lean-type pig breeds. Notably, four (g.3087C>T, g.3108C>T, g.3398C>T and g.3971A>C) of them were significantly associated with meat quality and composed a CCCA haplotype for fat-type pigs and TTCC haplotype for lean-type pigs. It was identified that MEG3-TTCC expressed higher than MEG3-CCCA in transcription level (P > 0.01) by using qRT-PCR. Results of stability assay showed that the lncRNA stability of MEG3-TTCC was lower than MEG3-CCCA (P > 0.05). Furthermore, the results of qRT-PCR, western blot and Cell Counting Kit-8 (CCK-8) assays demonstrated that overexpression of MEG3-TTCC more significantly inhibited the proliferation of porcine skeletal muscle satellite cells (SCs) than that of MEG3-CCCA (P > 0.05). Moreover, the results also reflected that overexpression of MEG3-TTCC more significantly promoted the differentiation of SCs than that of MEG3-CCCA (P > 0.05). In addition, western blot assay suggested that overexpression of MEG3-TTCC and MEG3-CCCA inhibited the proliferation of SCs by inhibiting PI3K/AKT and MAPK/ERK1/2 signaling pathway. Meanwhile, overexpression of these two haplotypes promoted the differentiation of SCs by activating JAK2/STAT3 signaling pathway in different degree. These data were valuable for further studies on understanding the crucial role of lncRNA in skeletal muscle development.